Center for geospace storms graduate student workshop - Keesee, Amy; Merkin, Viacheslav G.; Wiltberger, Michael; Hale, Stephen; Winter, Eric; Rao, Nikhil (Frontiers in Astronomy and Space Sciences, 2025)
The US National Aeronautics and Space Administration (NASA) DRIVE Center for Geospace Storms (CGS) hosted a workshop for graduate students conducting research in geospace science in November 2024. The research relevant to geospace has traditionally been separated into the Magnetosphere, including Magnetosphere-Ionosphere coupling, and the Ionosphere-Thermosphere-Mesosphere disciplines. This is apparent in sections of the American Geophysical Union and the funding structure of the United States National Science Foundation (NSF) and NASA. Following that structure, the geospace science community is divided into sub-communities separated along the discipline boundaries. However, it is now widely accepted that geospace is a tightly coupled system whose parts are strongly interconnected. The future Heliophysics workforce, particularly those focused on geospace, must have an understanding of how the regions of geospace influence and are influenced by each other. The goal of the workshop hosted by CGS was to bring together graduate students to improve their understanding across all regions of geospace with an emphasis on how to use geospace modeling to address compelling research questions throughout the domain. We report on the content of the workshop and the evaluation of achievement of these goals.